(untitled) (Quinto Sol, 2023)
We propose to address the continuities and transformations of the practices and circulation of art and cult objects that make up the patrimonial heritage of the church of San Ignacio in Buenos Aires during the first half of the 19th century –thus including the years after the expulsion of the Society of Jesus and its brief return to Río de la Plata during Juan Manuel de Rosas´s government–. This process operates as a double movement, tending, on one hand, to desacralize the Church and, on the other, to restore its central place for Christian worship. The sources analysis shows that, before and after the return of the Order, San Ignacio occupied a central place within the frameworks of the city, as well as an area of power dispute. We also propose to delimit the specific role played by the then governor Rosas, as well as the Jesuit Superior, Mariano Berdugo, in the construction of this process. We also consider that this course allows us to demonstrate a broader picture in which religious images and practices take on an active and relevant place, in contrast to the way in which art historiography usually characterizes this period as desecrated.